A local mesh free method with the singularity subtraction technique. (July 2019) - Oliveira, T.; Portela, A.
Abstract: The paper is concerned with a local mesh free numerical model (ILMF) developed to solve two-dimensional problems in linear elastic fracture mechanics. Based in the work theorem, the model formulation considers the approximation of the elastic field with moving least squares (MLS) and implements a reduced numerical integration, to improve the model accuracy. Linear elastic fracture mechanics applications of ILMF use the singularity subtraction technique (SST) which regularizes the elastic field, before the numerical solution, thus introducing the stress intensity factors (SIF) as additional primary unknowns of the problem. Hence, the numerical model performs a direct computation of the SIF and does not require a refined discretization to obtain accurate results which, therefore, is an efficient model strategy. Benchmark problems were solved, for an assessment of the accuracy and efficiency of these techniques.